PENDIDIKAN ISLAM DAN BUDAYA PERSPEKTIF KH. ABDURRAHCMAN WAHID - Rufi’ah Rufi’ah; Saman Hudi (FAJAR Jurnal Pendidikan Islam, 2024)
This research examines Abdurrahman Wahid (Gus Dur)'s views on the role and position of religion and culture in the life of the Indonesian nation, with an emphasis on the concept of "Islamic Indigenization." Islam, as a universal religion, interacts with and influences the cultural values and traditions of Indonesian society, particularly those originating from "Eastern Culture." This study aims to reveal the relationship between traditional cultural practices and Islamic teachings, as well as how Islamic principles are applied and adjusted to local customs. The findings show that the manifestation of Islamic teachings into local culture, according to Gus Dur, is based on two categories of Islamic teachings: first, the foundational values, which include justice, equality, and democracy; and second, the teachings in the form of their operational framework. The operational framework in Islamic teachings must be based on the welfare of humanity.